2008
DOI: 10.1016/j.chembiol.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Structure and Mode of Action of Microbisporicin, a Potent Lantibiotic Active Against Multiresistant Pathogens

Abstract: Antibiotics blocking bacterial cell wall assembly (beta-lactams and glycopeptides) are facing a challenge from the progressive spread of resistant pathogens. Lantibiotics are promising candidates to alleviate this problem. Microbisporicin, the most potent antibacterial among known comparable lantibiotics, was discovered during a screening applied to uncommon actinomycetes. It is produced by Microbispora sp. as two similarly active and structurally related polypeptides (A1, 2246-Da and A2, 2230-Da) of 24 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 35 publications
4
161
0
1
Order By: Relevance
“…2B). Moreover, microbisporicin has a similar N-terminal structure to that of nisin, but is produced by Actinobacteria (22,23), and its LanC does not even belong to group 3, which harbors most enzymes for nisin-like lanthipeptides. These results demonstrate convergent evolution to arrive at nisin-like architectures.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Moreover, microbisporicin has a similar N-terminal structure to that of nisin, but is produced by Actinobacteria (22,23), and its LanC does not even belong to group 3, which harbors most enzymes for nisin-like lanthipeptides. These results demonstrate convergent evolution to arrive at nisin-like architectures.…”
Section: Resultsmentioning
confidence: 99%
“…Among the Antibiotic discovery in the twenty-first century S Donadio et al new lantibiotics identified, the most active compound was NAI-107 (Figure 2a), produced by Microbispora sp. 39 This compound represents the first example of a class I lantibiotic produced by actinomycetes. It is currently a developmental candidate for the treatment of nosocomial infections by Gram-positive pathogens.…”
Section: Improved Variants From Microbial Sourcesmentioning
confidence: 99%
“…pIJ12321 was PCR targeted to introduce an integrase (int⌽C31), phage attachment site (attP), origin of transfer (oriT), and apramycin resistance cassette [aac(3)IV], creating pIJ12323. (3) and microbisporicin (4). Residues are unmodified (white), dehydrated (purple), dehydrated and cyclized (blue), or modified in other ways (green).…”
Section: Methodsmentioning
confidence: 99%
“…1B) (3) and suggested that planosporicin was indeed ribosomally synthesized. Evidence thus far indicates that planosporicin inhibits cell wall biosynthesis (22), and its N-terminal similarity to nisin (23) and microbisporicin (4) suggests an ability to bind to lipid II, the immediate precursor for cell wall biosynthesis (24). Planomonospora is a genus in the family Streptosporangiaceae with a high genomic GC content that forms a highly differentiated, branched mycelium that sporulates to form clavate monospores (25).…”
mentioning
confidence: 99%